Equivalence of the cholecystographic results obtained successively in the same subjects with intravenous tretraiod and with phenylpropionic iodine orally - Varela Fuentes, B.; Zubiaurre, L; Hojman, I (Cirugía del Uruguay, 2020)
Presented at session 24th October 1945